Negotiating the Local and Global in Nepalese EAP: Inherent Ideological Tensions and Possible Pathways - Kafle, Madhav (Journal of NELTA, 2015)
This article explores ideological tensions and possible directions to solutions in Nepalese EAP pedagogy in the context of increasingly interdependent world. Seventeen EAP professionals responded to a qualitative online survey disseminated through the Nepal English Language Teachers’ Association listserv, personal emails and other social networking sites. Data was analyzed from the perspective of language ideologies. The main ideological tensions as indicated by the teachers are grouped under three interrelated headings: top-down imposition, buying into Standard English as a panacea for all problems, and disconnect between policy and practice. Based on these findings, the article argues that whereas the top-down imposition is connected with the ideology of development, buying into Standard English with ideologies of linguistic fixity and purism, and the disconnect between policy and practice with the ideology of nationalism and language ownership. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12082 Journal of NELTA, Vol 19 No. 1-2, December 2014: 77-87